Analysis on the instrumental and experiential attitudes towards bribery among youths from different types of primary and secondary schools in Malaysia - Mengzhen, Lim; Wan Jaafar, Wan Munira; Mohd Khir, Azlina; Hamsan, Hanina Halimatusaadiah (Human Resource Management Academic Research Society, 2021)
Attitudes explain a wide range of behaviours including bribery. As the education environment plays a crucial role in communicating messages about what behaviour is acceptable, the ways we structure our school system could potentially influence how attitudes are shaped. In Malaysia, students attended different types of primary and secondary school (e.g. national and vernacular). Thus, this study aimed to explore the instrumental and experiential attitudes towards bribery of students attended four different types of primary and secondary schools. There were 198 Malaysian youths with an age range of 18 to 29 (M = 20.43) participated in this study. Instrumental and experiential attitudes towards bribery scales were used to measure both variables. Kruskal-Wallis test was used and the results indicated that there were no significant differences found between instrumental attitudes or experiential attitudes towards bribery among youths from four different types of schools selected in this study. However, some respondents claim that offering a small amount of money is more acceptable than offering a large amount of money. The implied that the acceptability of a dishonest act depends on its seriousness.